Evaluation of model nesting performance on the Texas‐Louisiana continental shelf. Issue 5 (15th May 2013) - Marta-Almeida, Martinho; Hetland, Robert D.; Zhang, Xiaoqian
Abstract : [1] A skill assessment of a model of the Texas‐Louisiana shelf, nested in a variety of different parent models, is performed using hydrographic salinity data. The nested models show improved salinity skill compared to the same model using climatological boundary conditions, as well as general skill score improvements over the parent models in the same region. Although a variety of parent models are used and these parent models have widely different skill scores when compared with regional hydrographic data sets, the skill scores for the nested models are generally indistinguishable. This leads to the conclusion that nesting is important for improving model skill, but it does not matter which parent model is used. The model is also used to create a series of ensembles, where the local forcing is varied with identical boundary conditions and where the boundary conditions are varied by nesting within the various parent models. The variance in the ensemble spread shows that there is a significant level of unpredictable, nonlinear noise associated with instabilities along the Mississippi/Atchafalaya plume front. The noise is seasonal and is greatest during summer upwelling conditions and weaker during nonsummer downwelling. Key Points: Nested model of the Texas‐Louisiana shelf Evaluation of different parent models nesting with model skill Instabilities along the Mississippi/Atchafalaya plume front